A coupled homogenisation-damage model for masonry cracking - Zucchini, Alberto (2004)
Cracking is responsible for the vast majority of masonry non-linear behaviour, due to the low tensile strength of the material. Masonry features orthotropic behaviour with material axes normal and parallel to the bed joints, being the response straightforward for tension normal to the bed joints and rather complex for tension parallel to the bed joints. This paper addresses the formulation and implementation of coupling between a micro-mechanical homogenisation model and an isotropic damage model for the masonry components. The non-linear homogenisation formulation requires an improved internal deformation mode of the masonry basic cell, with respect to previous works. Finally, the model is validated with a comparison with numerical results available in the literature, using interface modelling.